Effects of different roughness elements on friction and pressure drop of laminar flow in microchannels. Issue 7 (2nd July 2018) - Lalegani, Fakhrodin; Saffarian, Mohammad Reza; Moradi, Ahmadreza; Tavousi, Ebrahim
Abstract : Purpose: According to very small dimensions of the microchannels, producing a microchannel with smooth surfaces is approximately impossible. The surface roughness can have a specific effect on microchannel performances. This paper aims to investigate the changes in friction and pressure drop in the microchannels by considering the different roughness elements on microchannel wall and changes in elementary geometry and flow conditions. Results show a significant effect of roughness on the pressure drop and friction. Design/methodology/approach: Two-dimensional fluid flow in the rough microchannels is analyzed using FLUENT . Microchannels have a height of 50 µm. Water at room temperature (25°C) has been used as working fluid. The Reynolds numbers are considered in laminar flow range and from 50 to 300. Findings: The results show that the value of friction factor reduces nonlinearly with an increase in Reynolds number. But, the pressure drops and the Poiseuille number in the microchannels increase with an increase in Reynolds number. The values of the pressure drop and the friction factor increase by increasing the height and size of the roughness elements, but these values reduce with an increase in the distance of roughness elements. Originality/value: The roughness elements types in this research are rectangular, trapezoidal, elliptical, triangular and complex (composed of multiple types of roughness elements). The effects of the Reynolds number, roughness height, roughness distance and roughness size on the pressure drop and friction in the rough microchannels are investigated and discussed. Furthermore, differences between the effects of five types of roughness elements are identified.